EKSPLORASI STILASI ORNAMEN PADA MONUMEN JAYANDARU SEBAGAI MOTIF KHAS SIDOARJO - Ega Khansa Alifa; Ardo Bernando (Universitas Mercu Buana, 2021)
Icons are very influential in the branding role of a city. With the icon owned by the city, it will help people to get to know the city better such as the city of Jakarta which has a Monas (National Monument) as its icon, as well as the city of Surabaya with statues of Sura and Baya. Sidoarjo also has a distinctive icon that is Jayandaru Monument located in Sidoarjo Square Jayandaru Monument is a monument that has the form of visualization of shrimp statues, milkfish and cracker ornaments depicting Sidoarjo Regency as a MSME area producing shrimp, milkfish and krupuk making centers. The purpose of the construction of Jayandaru Monument is as an icon of the city and to introduce the potential of sidoarjo area, namely the producers of milkfish, shrimp and cracker centers. One of the efforts to introduction the icon of Jayandaru Monument as a typical icon of Sidoarjo Regency is to make the main ornament of Jayandaru Monument, namely the icon of milkfish, shrimp and crackers as the main inspiration in the exploration of ornaments. Exploration techniques used are stilation techniques that are the cultivation of forms or depictions of natural forms that are innovated into different forms but do not leave the character of the original form.